Establishment size and the dispersion of wages: evidence from European countries - Thierry Lallemand; François Rycx (Institute for the Study of Labor (IZA), 2005)
We investigate how the wage distribution differs among small and large establishments in four European countries. Findings show that within-establishment wage dispersion rises with size because large employers have a more diverse workforce. They also suggest that screening and monitoring costs imply a lower sensitivity of wages to ability in larger establishments. Smaller establishments are found to rely more on incentive-based pay mechanisms, particularly in countries with a low trade union coverage rate. Further results indicate that between-establishment wage dispersion decreases with employer size because smaller establishments are technologically more diversified and hence exhibit greater diversity in average workforce skills.
Keywords: J21; J31; 330; wage structure; establishment size; decomposition of wages; Europe; Lohnstruktur; Betriebsgröße; Schätzung; Belgien; Irland; Italien; Spanien